Pediatric Access and Continuity of HIV Care Before the Start of Antiretroviral Therapy in Sub-Saharan Africa. Issue 9 (September 2016) - Bastard, Mathieu; Poulet, Elisabeth; Nicolay, Nathalie; Szumilin, Elisabeth; Balkan, Suna; Pujades-Rodriguez, Mar
Abstract : Background: The number of HIV-infected children starting antiretroviral treatment (ART) has increased in resource-limited settings during the past decades. However, there are still few published data on the characteristics of pediatric patients at program enrolment and on the dynamics of dropping out before the start of ART. Methods: We performed a retrospective cohort study among HIV-infected pediatric patients (age, 5–14 years) not yet started on ART enrolled in 4 HIV sub-Saharan African programs. Descriptive and risk factors for mortality and lost to follow-up (LFU) were investigated using adjusted parametric or Cox proportional hazard models. Results: A total of 2244 patients (52.8% girls) were enrolled in HIV care, a median of 2 days [interquartile range (IQR), 0–8 days] after HIV diagnosis. Baseline median CD4 cell count was 409 cells/μL (IQR, 203–478 cells/μL); 43% were in clinical stage 3 or 4, 71% required ART and 76.2% of these patients initiated therapy. Of those eligible not started on ART, 14% died and 59% were LFU. Median pre-ART follow-up was 4.4 months (IQR, 1.3–20 months) and was shorter for eligible patients. Mortality rates were 6.2 of 100 person-years [95% confidence interval (CI), 4.6–8.3] in the 0- to 6-month period and 1.3 of 100 person-years (95% CI, 0.9–2.0) in the 6- to 60-month period. LFU rates were 37.4 of 100 (95% CI, 33.0–42.4) and 8.3 of 100 person-years (95% CI, 7.1–9.8), respectively. Advanced HIV disease at presentation (low body mass index, stage 3 or 4, low CD4 count or tuberculosis diagnosis) was associated with increased mortality and LFU. Conclusions: Late presentation and delays in initiating ART among eligible children were responsible for the large incidence of patient losses during pre-ART follow-up in sub-Saharan Africa.